ANALYSIS OF THE EXTERNAL SURFACE OF CORONAL SEALERS USED IN ATRAUMATIC RESTORATIVE TREATMENT (CIPEEX, 2025)
The external surface of three glass ionomer cements (GIC) used in atraumatic restorative treatment (ART) was analyzed: Vitro Molar, Ketac Cem Easymix, and Riva Self Cure. Specimens were prepared using polyethylene tubes (3 mm x 3 mm) and processed for scanning electron microscopy (SEM) analysis. Images with 5000x magnification were obtained, and the external surface of the tested materials was qualitatively evaluated regarding its regularity or irregularity, chemical element distribution, particle shape, and size. The NSS Spectral Analysis System 2.3 software was used to measure the chemical components present on the external surface of the GICs, and the element distribution maps were obtained using the NetCounts method. Vitro Molar cement showed an irregular external surface with non-uniform element distribution, globular particles of different sizes, and was mainly composed of aluminum (Al) and silica (Si). A small amount of fluoride (F) was observed. Ketac Cem Easymix cement exhibited a regular surface with uniform element distribution, globular particles, and was primarily composed of Al, Si, and calcium (Ca). The Riva Self Cure cement displayed a regular external surface with uniform element distribution, small spherical particles, and had Si and Al as the main chemical components. Different morphological and compositional aspects were observed in the tested materials. Fluoride was observed only in Vitro Molar cement.
Keywords: glass ionomer cements; chemical compounds; edx